Design method of double freeform surface lens with diffuse reflection. (April 2020) - Zhu, Z; Peng, B; Yuan, J; Xu, X
The design method of a double freeform surface lens is being widely applied in non-imaging optical systems. In this paper, a diffuse reflection freeform surface is introduced into the design of a double freeform surface lens. Different from the universal double freeform surface lens, this double freeform surface lens is divided into a small-angle freeform surface and a large-angle diffuse reflection freeform surface. The small-angle freeform surface firstly limits and forms the lighting area. Then, the large-angle freeform surface is designed to improve the efficiency of lighting the area. And this front light diffuse reflection effectively avoids the influence of light source projection onto the lighting effects. Based on this design method, the double freeform surface lens is obtained. The results show that the efficiency of a circular lighting area reaches 81% and the uniformity of the irradiance distribution reaches 91%. And this design is also suitable for forming different shapes of lighting areas while maintaining a better lighting effect.